Evaluasi Ketahanan terhadap Kekeringan Beberapa Aksesi Jagung Lokal Bali - Pradnyawathi, Ni Luh Made; Mayun, Ida Ayu; Wijana, Gede; Soniari, Ni Nengah (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024)DO - 10.24843/AJoAS.2024.v14.i03.p08, 2024)
Evaluation of Drought Resistance Some Local Bali Corn Accessions. To produce maize varieties adaptive to drought stress, many maize genotypes must be selected and grown under normal and drought-stressed conditions to evaluate their response to these conditions properly and effectively. This study aimed to determine the drought resistance properties of several local Balinese maize accessions resulting from Exploration activities. The research was conducted at the Experimental Farm, Faculty of Agriculture, Jalan Pulau Moyo, Denpasar Bali. The design used in this study was a simple Randomized Group Design (RAK). The treatments were nine local Balinese corn accessions from the exploration, which were planted under normal and drought-stressed conditions with 3 (three) replications so that there were 54 experimental plots. Data were analyzed in the form of index values against the treatment without stress (normal) of each accession with the formula NI = observation value on plants with stress /observation value on plants without stress. Data were analyzed statistically according to the design used.  If the treatment has a significant effect, it is further tested with DMRT at the 5% level. Almost all variables observed showed no significant differences between the accessions tested except for the 1000 seed weight variable. All accessions tested had index values close to one and some even exceeded one, which means that given the drought treatment, the yield decline was not too high and some even gave higher yields than normal conditions. seen from the weight of 1000 seeds, Putih Pangkung Paruk and Putih Purwakerti were the most sensitive accessions to drought.